2014
DOI: 10.1159/000363514
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Prognostic Implications of Orthostatic Hypotension in Older Individuals with Mild-to-Moderate Dementia

Abstract: Aim: To study the course and prognostic implications of orthostatic hypotension (OH) in older individuals with mild-to-moderate dementia. Methods: Referrals to outpatient clinics specialising in old age psychiatry and geriatric medicine in the counties of Rogaland and Hordaland in western Norway with a first-time diagnosis of mild dementia were consecutively asked for inclusion. A total of 211 participants underwent a comprehensive baseline assessment with annual follow-ups. Patients with OH at both baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…13 Our results are consistent with those of other longitudinal studies that found no differences in MMSE score between subjects with and without orthostatic hypotension at 2-and 4-year follow-up. 12,29 Our data suggest that the association found in other reports between orthostatic hypotension and CD may be the consequence of other factors or conditions that share the same pathogenesis as orthostatic hypotension.…”
Section: Orthostatic Hypotension Does Not Predict Cognitive Degenerationsupporting
confidence: 61%
See 2 more Smart Citations
“…13 Our results are consistent with those of other longitudinal studies that found no differences in MMSE score between subjects with and without orthostatic hypotension at 2-and 4-year follow-up. 12,29 Our data suggest that the association found in other reports between orthostatic hypotension and CD may be the consequence of other factors or conditions that share the same pathogenesis as orthostatic hypotension.…”
Section: Orthostatic Hypotension Does Not Predict Cognitive Degenerationsupporting
confidence: 61%
“…13 Our results are consistent with those of other longitudinal studies that found no differences in MMSE score between subjects with and without orthostatic hypotension at 2-and 4-year follow-up. 12,29 Our data suggest that the association found in other reports between orthostatic hypotension and CD may be the consequence of other factors or conditions that share the same pathogenesis as orthostatic hypotension.30 It may also be that different results stem from different groups being compared (we only compared our participants with orthostatic hypotension with participants who had normal postural changes in BP, whereas other studies compared them with participants who had orthostatic hypertension too). A final consideration concerns the finding that orthostatic hypotension was associated with a higher mortality rate than orthostatic hypertension, though this association disappeared after correcting for potential confounders.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Studies examining orthostatic BP changes and cognition are less consistent than studies of other health outcomes. Associations between orthostatic hypotension and cognitive decline in the elderly have been demonstrated in at least one study, while others have failed to find associations . These studies have all been conducted in elderly populations and focused on cognitive impairment according to performance on a global screening measure, such as the Mini‐Mental State Examination.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 32 included studies, 18 reported a positive association between OH and worse cognition, based on either cognitive test score (Otsuka et al, 2014;Aydin et al, 2017;Allcock et al, 2006;Pilleri et al, 2013;Bengtsson-Lindberg et al, 2015;Frewen et al, 2014;Huang et al, 2017;Centi et al, 2017;Coutaz et al, 2012;Matsubayashi et al, 1997;Mehrabian et al, 2010;Peralta et al, 2007) or diagnosis of dementia (Hayakawa et al, 2015;Elmstahl and Widerstrom, 2014;Kim et al, 2012;O'Hare et al, 2017a;Sonnesyn et al, 2009;Wolters et al, 2016a) and 14 studies reported no association (Biogeau et al, 2017;Schoon et al, 2013;Umehara et al, 2016;Idiaquez et al, 2007;Agnoletti et al, 2015a;Bouhanick et al, 2014;Curreri et al, 2016;Punchick et al, 2016;Soennesyn et al, 2014;Soysal et al, 2014;Viramo et al, 1999;Yap et al, 2014;Asensio Lafuente et al, 2011;Feeney et al, 2016).…”
Section: Systematic Reviewmentioning
confidence: 99%